Multi-site and multi-depth near-infrared spectroscopy in a model of simulated (central) hypovolemia: lower body negative pressure - Bartels, Sebastiaan A. (Springer-Verlag, 2011)
PURPOSE: To test the hypothesis that the sensitivity of near-infrared spectroscopy (NIRS) in reflecting the degree of (compensated) hypovolemia would be affected by the application site and probing depth. We simultaneously applied multi-site (thenar and forearm) and multi-depth (15–2.5 and 25–2.5 mm probe distance) NIRS in a model of simulated hypovolemia: lower body negative pressure (LBNP). METHODS: The study group comprised 24 healthy male volunteers who were subjected to an LBNP protocol in which a baseline period of 30 min was followed by a step-wise manipulation of negative pressure in the following steps: 0, −20, −40, −60, −80 and −100 mmHg. Stroke volume and heart rate were measured using volume-clamp finger plethysmography. Two multi-depth NIRS devices were used to measure tissue oxygen saturation (StO2) and tissue hemoglobin index (THI) continuously in the thenar and the forearm. To monitor the shift of blood volume towards the lower extremities, calf THI was measured by single-depth NIRS. RESULTS: The main findings were that the application of LBNP resulted in a significant reduction in stroke volume which was accompanied by a reduction in forearm StO2 and THI. CONCLUSIONS: NIRS can be used to detect changes in StO2 and THI consequent upon central hypovolemia. Forearm NIRS measurements reflect hypovolemia more sensitively than thenar NIRS measurements. The sensitivity of these NIRS measurements does not depend on NIRS probing depth. The LBNP-induced shift in blood volume is reflected by a decreased THI in the forearm and an increased THI in the calf. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00134-010-2128-6) contains supplementary material, which is available to authorized users.